2010
DOI: 10.1055/s-0029-1219374
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Synthesis of Substituted 1,3-Oxazoles

Abstract: The halogen dance isomerization is a facile and preparatively effective pathway for the synthesis of 2,4,5-trisubstituted-1,3-oxazoles. Keywords oxazoles; halogen dance rearrangement; alkylationIn recent years, structural elucidation studies of biologically significant natural products have frequently incorporated novel 1,3-oxazole ring systems within complex molecular architectures. Numerous examples include hennoxazole A, 1 phorboxazoles A and B, 2 diazonamides A and B, 3 rhizopodin, 4 telomestatin, 5 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…11 Furthermore, we have shown that 5-bromo-2-(phenylthio)-1,3-oxazole ( 8) undergoes a facile base-induced isomerization, characterized as a halogen dance rearrangement to provide access to the 4-bromo-1,3-oxazole 11 (85%). 13 In this letter, we have described a survey of Suzuki and Stille cross-coupling reactions, which demonstrate the utility of these derivatives for a convenient general preparation of 2,5-and 2,4-disubstituted oxazoles. In addition, we have documented the use of sodium hydrosulfite for reductive desulfonylations to yield C-4 and C-5 monosubstituted 1,3-oxazoles.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…11 Furthermore, we have shown that 5-bromo-2-(phenylthio)-1,3-oxazole ( 8) undergoes a facile base-induced isomerization, characterized as a halogen dance rearrangement to provide access to the 4-bromo-1,3-oxazole 11 (85%). 13 In this letter, we have described a survey of Suzuki and Stille cross-coupling reactions, which demonstrate the utility of these derivatives for a convenient general preparation of 2,5-and 2,4-disubstituted oxazoles. In addition, we have documented the use of sodium hydrosulfite for reductive desulfonylations to yield C-4 and C-5 monosubstituted 1,3-oxazoles.…”
Section: Methodsmentioning
confidence: 98%
“…However, the well-behaved carbanion from 7 (Scheme 3, R = SO 2 Ph, X = Li) facilitates convenient halogenation and stannylation reactions yielding 9 and 10 , respectively 11. Furthermore, we have shown that 5-bromo-2-(phenylthio)-1,3-oxazole ( 8 ) undergoes a facile base-induced isomerization, characterized as a halogen dance rearrangement to provide access to the 4-bromo-1,3-oxazole 11 (85%) 13. In this letter, we have described a survey of Suzuki and Stille cross-coupling reactions, which demonstrate the utility of these derivatives for a convenient general preparation of 2,5- and 2,4-disubstituted oxazoles.…”
mentioning
confidence: 95%
“…Among several known methods for the preparation of 4bromooxazoles, [2,4,30,32,35,[50][51][52][53] we have turned our attention to the LDA-mediated halogen dance reaction of 2-substituted 5bromooxazoles (Scheme 3). [54][55][56] Thus, the advantage of abovedescribed one-pot reaction sequence for the preparation 5bromooxazole (10) might be taken for the synthesis of the previously unknown 4-bromo derivative (11), if LDA-mediated halogen dance step would be added (Scheme 4). It is interesting to note that unlike 2-TIPS-5-bromoxazole (34), isomeric 2-TIPS-4-bromoxazole (35) could be isolated from the reaction mixture, and it was stable at r.t. Due to this reason, its chromatographic purification became possible, which gave the product 35 in 46 % yield.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al have shown that 4-bromo-5iodo-2-(phenylsulfanyl)oxazole can be accessed in a halogen dance reaction starting from easily accessible 5-bromo-2-(phenylsulfanyl)oxazole. 8 The sequence is believed to start by deprotonation at C4 followed by 1,2-migration of the halo substituent to the 4-position, placing the negative charge at C5. 9 In a similar manner, Stambuli et al accessed disubstituted 2-aryl-4-alkenyloxazoles after a halogen dance reaction starting from 2-(n-butylsulfanyl)-5-iodooxazole.…”
mentioning
confidence: 99%
“…The 4-alkenyl side chain could be introduced in Pd-catalyzed cross coupling reaction. Williams et al have shown that 4-bromo-5-iodo-2-(phenylsulfanyl)­oxazole can be accessed in a halogen dance reaction starting from easily accessible 5-bromo-2-(phenylsulfanyl)­oxazole . The sequence is believed to start by deprotonation at C4 followed by 1,2-migration of the halo substituent to the 4-position, placing the negative charge at C5 .…”
mentioning
confidence: 99%